Efeitos de características das cavernas sobre a comunidade de morcegos cavernícolas no cárste da Bodoquena, Mato Grosso do Sul - ALÉXIA MURGI LEONARDO (2025)
Caves are an important part of terrestrial ecosystems because they contain rich and unique biological communities, especially when there is input of organic matter brought by inhabiting bats. In this study, I describe the fauna of cave bats in the karst region of Serra da Bodoquena, as well as the effects of physical characteristics of caves on the abundance, richness, and composition of bat species. I sampled 17 caves that covered the structural variation of caves in the region, and mistnetted bat individuals at the cave entrances. Physical measurements of the caves were taken in the field or obtained from available maps. A total of 361 individuals from 15 species and four families were recorded. Each cave contained between two and eight species of bats (4.8 ± 1.79; mean ± SD). Caves at lower elevations, containing higher rooms, and narrower and more protected entrances contained an increased abundance of bats. Bat species richness decreased with increasing entrance width, and bat species composition per cave was influenced by altitude, entrance width, maximum height, entrance exposure, and cave length. The results support a high diversity of cave bats in the Serra da Bodoquena, as well as a differential occupation of caves by bat species according to their internal and external characteristics. The results provide broad knowledge of the cave bat fauna in the region, and can contribute to the planning of conservation actions in the Serra da Bodoquena.